Acceptance of the Methods of Decision-making: A Case Study from Software Development Companies in Ukraine and Malaysia - Mezhuyev, Vitaliy; Lytvyn, Oleg M.; Pershyna, Iuliia; Nechuiviter, Olesia; Lytvyn, Oleg O.; Lavrik, Vladimir (ACM Digital Library, 2019)
Any software development company encounters issues that need decision-making. At the same time, the use of reliable and proven methods of decision-making does not become a common practice in software companies worldwide. The issues here are the need for extra staff training, allocation of additional time, and inertia of the software industry. This research studies the problems of adoption of the methods of decision-making in the software development companies of Ukraine and Malaysia. The survey was conducted to evaluate software engineers' attitudes toward the use of the methods of decision-making. Research outcomes can be used to raise the level of adoption of the methods of decision-making in software companies worldwide.